UZBEKISTAN AND TURKMENISTAN WITHINTHE FRAMEWORK OF INTERNATIONALCOOPERATION - Nurmanov Shahzodbek Mahmadoli ugli (Western European Studies, 2025)
As a full-fledged member of the international community, the Republic of Uzbekistan has prioritized foreign policy and the development of bilateral and multilateral relations with countries around the world since the first days of its independence. The leadership of Uzbekistan has developed a strategy and principles of foreign policy and defined its priority directions. Accordingly, the Republic of Uzbekistan has designated the maintenance and development of equal cooperation with the countries of the Central Asian region as a key priority. Today, this direction is entering a new stage of influence.
Keywords: Foreign policy; Economic relations; Central Asia